EDITORIAL PAPER - MEDICAL TECHNIQUES - JT ADMIN (Journal of Techniques)
The last couple of decades have witnessed ground breaking advances in health and medical technology which has resulted in the improvement of disease diagnosis, monitoring of treatment and sustaining health. Health technology research could be in the form of procedures, vaccines, devices and systems as outlined by the world health organization in its Health technology assessment report. Scientists in the field of medical and health technology are continuously inventing new devices, improving existing procedures and developing new techniques in the hope of improving medical practice and health monitoring. Some of the latest research and innovations in health and medical techniques have made an impressive difference, saved and improved the quality of countless lives worldwide. Collaborative work from scientists all around the world is necessary to tackle current health problems faced by the growing world population. The journal of techniques hopes to attract a global audience by its commitment to publishing the latest innovations and techniques related to medical and health topics.